Lovastatin induces mitotic abnormalities in various cell lines - Lamprecht, Jan; Paweletz, Neidhard (Cell biology international, 2013)
We examined the effects of lovastatin, a common anti-atherosclerotic drug and a blocker of the cell cycle, on the process of mitosis. It is known that lovastatin induces an arrest or a retardation of the cell cycle in many cell types not only at the G1phase, but also at the G2/M transition. After 24-48h incubation of epithelial PtK2, T24, HeLa cells and fibroblastic L929 cells in the presence of 1.0-60.0μm lovastatin, diverse mitotic perturbations have been observed. The most noteworthy phenomena recorded were prometaphase retardation and chromosome lagging during metaphase and anaphase. After the recovery in lovastatin-free media, the cells continued mitosis without any disturbances. Mevalonic acid prevented the effects of lovastatin. We conclude that the effects were specific for lovastatin-induced inhibition of mevalonic acid synthesis. Immunofluorescence studies with anticentromeric antibodies suggested that one of the possible causes of the lovastatin-induced mitotic disorder could be an interference with the development and function of the centromeres.